Ritual y espacios de memoria en la Hispania antigua (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The diverse solutions that were put into practice through the uses of ritualism and the places of memory in the (re)construction and negotiation of identity among the peoples of ancient Iberia are the aim of this paper. Rituals and cultural memory in cemeteries and sanctuaries, the meaning and possible functions of images -specially on pottery-, writing as monu- mentalization of landscape, examples of symbolic recycling of spatial transference of mnemotópoi, as well as the cultic re-use of long-time abandoned places ara analysed.
Keywords: Ritual; Cultural Memory; Iberians; Celtiberians; Lusitanians; Writing; Symbolic Recycling; Romanization